Mechanisms, policies for business models based on industry 4.0 platform: International experience and lessons for Vietnam - Hoang Van Thu; Nguyen Hong Anh; Nguyen Huu Khanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
The Fourth Industrial Revolution (4.0) is creating new business models based on technological platforms such as the platform economy, e-commerce, digital financial services (fintech), artificial intelligence (AI), and blockchain. Countries around the world have been implementing various regulatory mechanisms and management policies to support innovation while ensuring transparency, fairness, and safety. This study analyzes international experiences regarding the mechanisms and management policies for new business models in the United States and Germany, thereby drawing lessons for Vietnam. Code: 25032001